2005
DOI: 10.1093/jb/mvi003
|View full text |Cite
|
Sign up to set email alerts
|

Parasporin-1, a Novel Cytotoxic Protein to Human Cells from Non-Insecticidal Parasporal Inclusions of Bacillus thuringiensis

Abstract: Pro-parasporin-1 is a parasporal inclusion protein of the non-insecticidal Bacillus thuringiensis strain A1190. Cytotoxic fragments, named parasporin-1, were generated from pro-parasporin-1 by trypsin digestion. Parasporin-1 was purified by a combination of chromatography procedures based on the cytotoxic activity to HeLa cells. Two different fragments of 15-kDa and 56-kDa were detected in the purified parasporin-1 fraction. These fragments were tightly associated with each other and could not be separated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 0 publications
3
50
0
5
Order By: Relevance
“…Furthermore, the parasporal proteins of these B. thuringiensis strains (J61 and J72) were previously reported (Obeidat et al, 2012) to exhibit no insecticidal activity against diptera and lepidoptera. This is in agreement with previous studies (Mizuki et al, 1999bLee et al, 2000;Yamashita et al, 2000;Ito et al, 2004;Okumura et al, 2004;Katayama et al, 2005;Hayakawa et al, 2007;Jung et al, 2007;Uemori et al, 2008;Yasutake et al, 2008;Nagamatsu et al, 2010) that clearly demonstrated that only non-insecticidal parasporal proteins can exhibit discriminating cytotoxicity against different cancer cell types. Unfortunately, activated parasporal proteins from all reference B. thuringiensis strains screened in this study did not exhibit selective cytotoxicity against target cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the parasporal proteins of these B. thuringiensis strains (J61 and J72) were previously reported (Obeidat et al, 2012) to exhibit no insecticidal activity against diptera and lepidoptera. This is in agreement with previous studies (Mizuki et al, 1999bLee et al, 2000;Yamashita et al, 2000;Ito et al, 2004;Okumura et al, 2004;Katayama et al, 2005;Hayakawa et al, 2007;Jung et al, 2007;Uemori et al, 2008;Yasutake et al, 2008;Nagamatsu et al, 2010) that clearly demonstrated that only non-insecticidal parasporal proteins can exhibit discriminating cytotoxicity against different cancer cell types. Unfortunately, activated parasporal proteins from all reference B. thuringiensis strains screened in this study did not exhibit selective cytotoxicity against target cells.…”
Section: Discussionsupporting
confidence: 93%
“…Mizuki et al (1999b) reported cytotoxicity against human leukemic T cells and other human cancer cells for parasporal proteins produced by some noninsecticidal B. thuringiensis strains. Moreover, it was found that these non-insecticidal Cry proteins, designated parasporins, are capable of preferentially killing cancer cells upon proteolytic degradation (Mizuki et al, 1999bYamashita et al, 2000;Ito et al, 2004;Okumura et al, 2004;Katayama et al, 2005;Hayakawa et al, 2007;Jung et al, 2007;Uemori et al, 2008;Yasutake et al, 2008;Nagamatsu et al, 2010). Six parasporin families, including 19 parasporin toxins isolated from B. thuringiensis strains, were identified by the Committee of Parasporin Classification and Nomenclature (Okumura et al, 2010;Wong, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we identified four parasporins from noninsecticidal B. thuringiensis strains. 20) Of these, PS-1, PS-2, and PS-3 correspond respectively to Cry31Aa, 9) Cry46Aa, 10) and Cry41Aa.…”
Section: Discussionmentioning
confidence: 99%
“…B. thuringiensis is a uniquely specific, safe, and effective biological insecticide that has been used for more than 50 years (3,30). The increased use of B. thuringiensis in biological control and its potential application in medicine have encouraged researchers to find novel strains with different toxic spectra or high specific activity and new functional genes of B. thuringiensis (13,22,26,28).There are two known classes of ␦-endotoxins in B. thuringiensis: the insect-specific insecticidal crystal (Cry) proteins and the Diptera-specific cytolytic (Cyt) proteins. The Cry proteins are encoded by cry genes, include more than 480 different genes belonging to 124 subgroups of 60 groups, and show variable degrees of sequence homology (see the B. thuringiensis [Bt] toxin nomenclature website at http://www.lifesci.sussex.ac .uk/home/Neil_Crickmore/Bt/).…”
mentioning
confidence: 99%